SEXUAL EXPLOITATION OF REFUGEE WOMEN IN INTERNATIONAL LAW AND DOMESTIC LAW - Dr. Sabah Sami Dawood (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The increase in the phenomenon of infighting and internal conflicts, and the dangerous phenomena and negatives that result from it, the most important of which are major displacement movements of refugees and migrants from places of conflict to neighboring countries or transit countries, making most of these people vulnerable to a great danger of being trafficked and subjecting them to multiple types of violations, among which is the subject of our discussion which is: Sexual exploitation of refugee women who have become extremely vulnerable to this kind of practices, which are not taking place by individual persons, or by gangs or organized crime groups only, but it is the most dangerous of all that has become the subject of practices committed by peacekeepers and aid workers. International workers within the scope of the United Nations .Moreover, many influential people, politicians and clerics issued a list of practicing this kind of behavior, taking advantage of the power (material or moral) they possess and influence, especially in cases of lack of oversight, accountability mechanisms, and the absence of the legislative and legal deterrent structure.